P053 Detection of sexually transmitted pathogens from sediment of first-void urine in patients from greater zagreb area. (14th July 2019) - Vranes, Jasmina; Jurcevic, Jakov; Knezevic, Jasna; Ticic, Vladimira; Ljubin-Sternak, Suncanica
Abstract : Background: First-void urine (FVU) is the preferred specimen for the diagnosis of sexually transmitted (ST) infections in men. The use of the invasive and painful urethral swabs is a major barrier to screening and a key factor in male nonattendance at genitourinary medicine clinics. The aim of this study was detection of ST pathogens from sediment of FVU of 822 men, collected instead of urethral swabs. Methods: All samples were stained, cultivated and used in multiplex polymerase chain reaction (PCR) test. The number of polymorphonuclear leukocytes (PMNL) was detected by microscopy. Results: Urethritis was confirmed in only 72/822 (8.76%) patients by detecting a significant number of PMNL in sediment of FVU, and etiologic diagnosis was established in 68/72 men with diagnosed urethritis. Chlamydia trachomatis was detected as the most common cause of urethritis (47.22%), followed by Mycoplasma genitalium (12.50%) and Neisseria gonorrhoeae (9.72%). In patients with nongonococcal urethritis (NGU), M. genitalium was found as the second most common NGU pathogen. Microbiological analysis was required the most frequently for screening and control purposes (340/822, 41.36%), and in patients with chronic prostatitis (105/822, 12.77% of all patients). ST pathogens were detected more frequently in patients with urethritis than in patients from other diagnostic groups (p<0.01), while Ureaplasma urealyticum was detected without statistically significant difference among different diagnostic groups of patients (p>0.05). Conclusion: Urethritis was confirmed in less than 10% of patients, and the most samples collected in routine of clinical praxis are from patients without urethritis. In patients with urethritis multiplex PCR test can detect etiology quickly and reliable in almost all cases from noninvasive sample. Disclosure: No significant relationships.